ANALISIS PERKIRAAN KEBUTUHAN BAHAN BAKU EKSTRAK COFEE COLD BREW DI PT. MORADI - Ruspendi; Nurmutia, Syahreen; Tukiyat; Misbah (Jurnal Sains Indonesia, 2022)
During the 2021 period, the total production of PT. Moradi often has advantages and disadvantages compared to the actual number of requests due to the availability of raw materials that are not suitable. Availability of raw materials in the right amount will support the smooth production process, so it is necessary to do proper forecasting. The forecasting process carried out in this study uses the methods of Moving Average, weighted Moving Average and exponential smoothing. From the calculation results, it is obtained that the estimated number of production needs for the next period using the Moving Average method is 220, the weighted Moving Average method is 218 and the exponential smoothing method is 212. Next is to compare the forecast error values ​​to determine one method to be used as basis for decision making. From the calculation of the error value, the most appropriate forecasting method is the exponential smoothing method = 0.3, with a Mean Absolute Deviation (MAD) value of 21.02, a Mean Square Error (MSE) of 656.95 and a Mean Absolute Percent Error (MAPE) value of 10%. , with the value distribution of the Tracking Signal control map, nothing crosses the upper limit of the UCL and the lower limit of the LCL.